Olasz Design. - Budapest Galéria, Budapest (Budapest : Budapest Galéria, 1989)
Salocchi, Claudio ; Vecchi, M. ; Trabucco, F. ; Giurgiaro, Giorgetto ; Gabbrielli, Luigi ; Orlandini, Paolo ; Lucci, Roberto ; Negrello, Lorenzo ; Scagnellato, Marcello ; Zanotto, Paolo ; Di Dato, Vincenzo ; Gecchelin, Bruno ; Takeda, Hiroko ; van Onck, Andries ; Pareschi, Gianni
Olasz Design, Budapest Galéria, junius 8 - julius 9, 1989
boek